(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Enuresis is a common and possibly underestimated condition. While 5-10% of school-aged children suffer from the condition, a lack of background knowledge may impede timely child-adapted and successful therapy. Currently, nocturnal enuresis is generally considered a multifactorial disease associated with a complex interaction of somatic, psychosocial, and environmental factors. This work studied the possible etiological factors of nocturnal enuresis and effectiveness of alarm therapy. The study showed that monosymptomatic nocturnal enuresis is more common in male children with positive family history of NE pointing to the possible hereditary factor in its pathogenesis. Bedwetting can be caused by a variety of reasons, including physiological and behavioral. Alarm plus desmopressin may reduce the number of wet nights a week compared with desmopressin alone.